Rare case of an 83-year-old woman with transrectal small bowel evisceration caused by spontaneous rectal perforation. Issue 2 (9th February 2022) - Wiesler, Benjamin; Linke, Katja Simone; Delko, Tarik
Abstract : Spontaneous rectal perforation with transanal small intestinal evisceration is a rare condition. We report the case of an 83-year-old woman with a rectal perforation and transanal prolapse of small intestine through the rectal opening who was treated with transanal reposition under general anaesthesia and open Hartmann's procedure. As part of the Hartmann's procedure, segmental resection of the perforated colon was performed. This case illustrates that spontaneous rectal perforation is a severe surgical emergency, which needs immediate reposition and resection of the perforated rectum.